Investigation of the peculiarities of oxidation of Ti/Al nanoparticles on heating to obtain TiO2/Al2O3 composite nanoparticles - Lozhkomoev, Aleksandr S.; Kazantsev, Sergey O.; Bakina, Olga V.; Pervikov, Alexander V.; Chzhou, Valeria R.; Rodkevich, Nikolay G.; Lerner, Marat I. (Journal of cluster science)
The creation of new nanomaterials with improved characteristics, as well as the development of new approaches to obtain such materials is an urgent task in science and technology. One of the promising directions in obtaining improved nanomaterials is the use of precursors in the form of multicomponent metal nanoparticles. Thermal oxidation of bimetallic Ti/ Al nanoparticles obtained by electrical explosion of wires was investigated in this work. Ti/Al nanoparticles have been found to be completely oxidized with the formation of composite TiO2/ Al2O3 nanoparticles after calcination at 900 °C. The formation of TiO2 phase with a rutile structure on heating to 500 °C, and the formation of TiO2 phases with a rutile and anatase structure, as well as α-Al2O3 on heating to 700 °C have been established, in addition to the residue of unoxidized metals. Complete oxidation of Ti/Al nanoparticles occurs when heated to 900 °C. The photochemical activity of TiO2/ Al2O3 composite nanoparticles obtained at 900 °C was studied. The degradation of methyl orange dye reached 55% under UV irradiation for 120 min.